Desenvolvimento do cluster de economia criativa na área central da cidade de São Paulo - Nascimento, Patrícia Danielle Gomes do (2015)
The present dissertation discusses the structuring of a technology-related creative economy cluster in the downtown region of São Paulo. The choice of this region, as well as of the creative economy as an impulse for the economic requalification and social re-occupation of the area, aims to tackle the downtown’s emptying issue, impelling entrepreneurship and the positioning of the region as a place for social gathering. In order to analyze the feasibility and adequacy of this proposal, the applied research method, comprising proceedings related to a brief literature review and also interviews with creative industry professionals, was chosen. The study of international and national cases, the study of the Brazilian regulation, the evaluation of the development level of creative industries in São Paulo and the reflection about the city vocations were considered in this method. Taking such background into account, the modeling of the technology cluster in the Creative District of Sé/República was designed, aiming to outline proposals that could be developed in the short, medium and long terms. Immediate actions, such as the branding of ongoing activities, as well as medium term measures, such as partnership agreements, and others mostly related to structuring processes, such as the requalification of spaces and projects, were proposed. All these measures aimed to optimize the municipal action in the search of downtown re-occupation and, consequently, in the attraction of investments for this region, in order to restrain the degradation process and leverage the process of placing São Paulo’s downtown back in its position of valuable economic and cultural nucleus for the municipality. By means of this work, it can be concluded that there are examples in Brazil and worldwide that can serve as an inspiration to the development of the action proposed and that the possibility of generating a positive impact, even in times of budgetary constraints, is quite plausible.